2016
DOI: 10.2166/wp.2016.092
|View full text |Cite
|
Sign up to set email alerts
|

The EU Floods Directive trickling down: tracing the ideas of integrated and participatory flood risk management in Sweden

Abstract: This study examines how the EU Floods Directive – an extensive and innovative legislative instrument for integrated and participatory flood risk planning in all EU member states – influences local flood risk management in one member state, Sweden. The study identifies that: many municipalities have received new knowledge; cross-sectoral organisational structures for water and flood risk issues at the local level are being formed or strengthened; and the flood risk issue has been elevated up the political agend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…As the levels of detail vary in the assessments of different studies [88], as do the management approaches in the nine Austrian provinces, implications for other regions are difficult to grasp. Likewise, authors of a Swedish study argue that specific recommendations are difficult to generalise from a case study perspective [25]. Although action was taken to fulfil requirements of the FD and generally efforts were made to improve FRM, a re-examination of this contribution will be required once the policy cycle ends in 2021 in order to assess whether an adaptation tipping point occurred.…”
Section: (4) Have Management Approaches Changed?mentioning
confidence: 99%
See 1 more Smart Citation
“…As the levels of detail vary in the assessments of different studies [88], as do the management approaches in the nine Austrian provinces, implications for other regions are difficult to grasp. Likewise, authors of a Swedish study argue that specific recommendations are difficult to generalise from a case study perspective [25]. Although action was taken to fulfil requirements of the FD and generally efforts were made to improve FRM, a re-examination of this contribution will be required once the policy cycle ends in 2021 in order to assess whether an adaptation tipping point occurred.…”
Section: (4) Have Management Approaches Changed?mentioning
confidence: 99%
“…While existing research has discussed the FD and its impacts in several countries [22,[24][25][26][27], there is a lack of research on whether innovative change has occurred through the implementation of the FD or not. Generally, in directives the power of obligation differs significantly, which can affect legal efficiency [28].…”
Section: Introductionmentioning
confidence: 99%
“…They also observed that most of the described consequences were tangible and direct; thus, intangible and indirect consequences of flooding were noticeably missing in the assessments. Other challenges related to implementing the FD in Sweden include, for example, a lack of trust that national authorities will provide necessary input for local flood risk managers (Becker, 2018) and unclear roles and mandates among key concerned actors such as municipalities (Hedelin, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…While it is actively implemented in EU member states, its implementation has also raised challenges related both to flood risk management (e.g., practical risk analysis and planning) and related governance (e.g., broader societal arrangements and processes); see Section 2.1. Such challenges relate, for example, to the diversification of strategies, adaptation, participation, (Gralepois, 2020), cooperation (Dieperink et al, 2016), lack of clear roles and responsibilities (Hedelin, 2016; Snel et al, 2020) as well as effective stakeholder engagement (e.g., Edelenbos et al, 2017; Pasquier et al, 2020) related to floods and their governance. Together, these challenges indicate a need for a better understanding of the social processes and actor relations in flood risk governance (e.g., Hartmann & Driessen, 2017).…”
Section: Introductionmentioning
confidence: 99%